Associations between perceived institutional support, job enjoyment, and intentions to work in the United Kingdom: national questionnaire survey of first year doctors - Lachish, Shelly (BMC Med Educ, 2016)
BACKGROUND: Identifying factors that improve job satisfaction of new doctors and ease the difficult transition from student to doctor is of great interest to public health agencies. Studies to date have focused primarily on the value of changes to medical school curricula and induction processes in this regard, but have overlooked the extent to which institutional support can influence new doctors’ enjoyment of and attitude to work. Here, we examine variation in the perceived level of support received by new medical graduates in the United Kingdom (UK) from their employer and whether this influences enjoyment of and attitudes to the first postgraduate year, and whether doctors who perceived a lower level of support were less inclined to intend a long term career in medicine in the UK. METHODS: All UK medical graduates of 2012 were surveyed in 2013 in a cross-sectional study, towards the end of their first post-graduate year (the ‘F1’ year of the 2-year Foundation Training Programme for new UK doctors). We used linear regression to assess whether the level of support doctors reported receiving from their employing Trust (Very Good, Good, Adequate, Poor, or Very Poor) was associated with the extent to which they enjoyed their F1 year. Similarly, we assessed the strength of associations between self-reported level of Trust support and doctors’ responses to 12 statements about fundamental aspects of their working lives, each assessed on a 5-point scale of agreement. Using χ(2) tests we examined whether doctors’ intentions to practise medicine in the UK varied with the level of support they reported receiving from their Trust. RESULTS: The response rate was 45 % (2324/5171). Of 2324 responding junior doctors, 63.8 % reported receiving ‘Very Good’ (23.6 %) or ‘Good’ (40.2 %) initial support from their Trust, while a further 27.4 % stated they received ‘Adequate’ support. ‘Poor’ support was reported by 5.8 % and ‘Very Poor’ support by 2.2 %. We found very strong positive associations between the institutional support doctors reported receiving and their enjoyment of the F1 year and their self-expressed attitudes to aspects of their first year of work. Crucially, doctors who reported receiving lower levels of support (‘Poor’ or ‘Very Poor’) were significantly less likely to express intentions to continue practising medicine in the UK. CONCLUSIONS: The provision of effective institutional support for graduate doctors may promote workplace satisfaction and could help safeguard the long-term retention of junior doctors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-016-0673-6) contains supplementary material, which is available to authorized users.